Pulsed-electron-beam processing of materials for medical applications; Russian Physics Journal; Vol. 56, iss. 10 - Koval N. N. Nikolay Nikolaevich; Teresov A. D.; Denisova Yu. A.; Denisova E. A.; Ivanov Yu. F. Yuriy Fedorovich (2014, 2014)
Title screen